Inflammation and In-Stent Restenosis: The Role of Serum Markers and Stent Characteristics in Carotid Artery Stenting - Wasser, Katrin (Public Library of Science, 2011)
BACKGROUND: Carotid angioplasty and stenting (CAS) may currently be recommended especially in younger patients with a high-grade carotid artery stenosis. However, evidence is accumulating that in-stent restenosis (ISR) could be an important factor endangering the long-term efficacy of CAS. The aim of this study was to investigate the influence of inflammatory serum markers and procedure-related factors on ISR as diagnosed with duplex sonography. METHODS: We analyzed 210 CAS procedures in 194 patients which were done at a single university hospital between May 2003 and June 2010. Periprocedural C-reactive protein (CRP) and leukocyte count as well as stent design and geometry, and other periprocedural factors were analyzed with respect to the occurrence of an ISR as diagnosed with serial carotid duplex ultrasound investigations during clinical long-term follow-up. RESULTS: Over a median of 33.4 months follow-up (IQR: 14.9–53.7) of 210 procedures (mean age of 67.9±9.7 years, 71.9% male, 71.0% symptomatic) an ISR of ≥70% was detected in 5.7% after a median of 8.6 months (IQR: 3.4–17.3). After multiple regression analysis, leukocyte count after CAS-intervention (odds ratio (OR): 1.31, 95% confidence interval (CI): 1.02–1.69; p = 0.036), as well as stent length and width were associated with the development of an ISR during follow-up (OR: 1.25, 95% CI: 1.05–1.65, p = 0.022 and OR: 0.28, 95% CI: 0.09–0.84, p = 0.010). CONCLUSIONS: The majority of ISR during long-term follow-up after CAS occur within the first year. ISR is associated with periinterventional inflammation markers and influenced by certain stent characteristics such as stent length and width. Our findings support the assumption that stent geometry leading to vessel injury as well as periprocedural inflammation during CAS plays a pivotal role in the development of carotid artery ISR.